Influence of transcutaneous electrical stimulation on heterotopic ossification: an experimental study in Wistar rats - Zotz,T.G.G. (2015)
Heterotopic ossification (HO) is a metaplastic biological process in which there is newly formed bone in soft tissues, resulting in joint mobility deficit and pain. Different treatment modalities have been tried to prevent HO development, but there is no consensus on a therapeutic approach. Since electrical stimulation is a widely used resource in physiotherapy practice to stimulate joint mobility, with analgesic and anti-inflammatory effects, its usefulness for HO treatment was investigated. We aimed to identify the influence of electrical stimulation on induced HO in Wistar rats. Thirty-six male rats (350-390 g) were used, and all animals were anesthetized for blood sampling before HO induction, to quantify the serum alkaline phosphatase. HO induction was performed by bone marrow implantation in both quadriceps of the animals, which were then divided into 3 groups: control (CG), transcutaneous electrical nerve stimulation (TENS) group (TG), and functional electrical stimulation (FES) group (FG) with 12 rats each. All animals were anesthetized and electrically stimulated twice per week, for 35 days from induction day. After this period, another blood sample was collected and quadriceps muscles were bilaterally removed for histological and calcium analysis and the rats were killed. Calcium levels in muscles showed significantly lower results when comparing TG and FG (P<0.001) and between TG and CG (P<0.001). Qualitative histological analyses confirmed 100% HO in FG and CG, while in TG the HO was detected in 54.5% of the animals. The effects of the muscle contractions caused by FES increased HO, while anti-inflammatory effects of TENS reduced HO.